Mediational role of coping with stress in relationship between personality and effectiveness of performance of soccer players - Kalinowski, P.; Bojkowski, L.; Sliwowski, R.; Wieczorek, A.; Konarski, J.; Tomczak, M.. (International Journal of Sports Science & Coaching, 2020)
There is a trend in soccer to ensure comprehensive player preparation including fitness, technical and tactical, as well as mental aspects. It has been emphasized many times that personality traits (neuroticism, conscientiousness, extraversion) are significant for the effectiveness of performance in soccer. The question of why these relations occur has been considered relatively rarely. Therefore, the aim of this study is an attempt to explain these relations through introduction of ways of coping with stress as their significant mediators. It is hence assumed that players with certain personality traits are characterized by specific ways of coping with stress which are related to the effectiveness of their performance. The study group consisted of 122 players, aged 16-19 years. The participants of the study were youth teams at the championship level (medalists of the youth Polish Championships), and the following research tools were used: NEO-FFI Personality Inventory, The Coping Inventory for Competitive Sport (CICS) and Szwarc`s Observation Sheet for effectiveness in soccer. It was demonstrated that task-focused ways of coping with stress (effort expenditure, thought control, and logical analysis) were the most frequent mediators of relations between the studied traits and the effectiveness of performance of soccer players.